2018
DOI: 10.1021/acs.nanolett.7b04981
|View full text |Cite
|
Sign up to set email alerts
|

Highly Surface-Active Ca(OH)2Monolayer as a CO2Capture Material

Abstract: Greenhouse gas emissions originating from fossil fuel combustion contribute significantly to global warming, and therefore the design of novel materials that efficiently capture CO can play a crucial role in solving this challenge. Here, we show that reducing the dimensionality of bulk crystalline portlandite results in a stable monolayer material, named portlandene, that is highly effective at capturing CO. On the basis of theoretical analysis comprised of ab initio quantum mechanical calculations and force-f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…For CO 2 capture, in general, two protocols can be used, post-combustion and pre-combustion. [2][3][4] Low-temperature sorbents (based on amines, silica, zeolites, carbon, and MOFs) are mainly used for postcombustion CO 2 capture from ue gas at low temperatures (25 to 75 C), while high-temperature sorbents are specically developed for pre-combustion capture between 500 and 700 C. [2][3][4] "Pre-combustion capture" is one of the most challenging but best ways to tackle climate change as CO 2 is captured during the process at high temperatures with ideally zero release into the environment. [5][6][7] Pre-combustion capture is potentially less expensive than post-combustion capture, as CO 2 gets captured as soon as it is produced during the process without releasing it into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…For CO 2 capture, in general, two protocols can be used, post-combustion and pre-combustion. [2][3][4] Low-temperature sorbents (based on amines, silica, zeolites, carbon, and MOFs) are mainly used for postcombustion CO 2 capture from ue gas at low temperatures (25 to 75 C), while high-temperature sorbents are specically developed for pre-combustion capture between 500 and 700 C. [2][3][4] "Pre-combustion capture" is one of the most challenging but best ways to tackle climate change as CO 2 is captured during the process at high temperatures with ideally zero release into the environment. [5][6][7] Pre-combustion capture is potentially less expensive than post-combustion capture, as CO 2 gets captured as soon as it is produced during the process without releasing it into the environment.…”
Section: Introductionmentioning
confidence: 99%
“…On the theoretical front, these efforts led to the prediction of 2D allotropes of group-IV elements, group IV, III-V, and II-VI compounds, [7][8][9][10][11][12][13][14][15] silicon dioxides, 16 transition metal dioxides 17,18 and dichalcogenides, 17,[19][20][21][22] monochalcogenides, [23][24][25] and alkali-earth metal hydroxides. 26,27 It was shown that these 2D materials display diverse electronic, optical, and magnetic properties for a wide range of technological applications, such as optoelectronics, spintronics, catalysts, chemical and biological sensors, supercapacitors, solar cells, nanotribology, [28][29][30] hydrogen production, and lithium or sodium ion batteries. 31,32 Very recently, the synthesis of ultrathin, 2D black phosphorus, through exfoliation from its layered bulk counterparts, has brought the suspended 2D monolayers and multilayers of group-VA elements [33][34][35] into the focus of current research.…”
Section: Introductionmentioning
confidence: 99%
“…The spontaneous reaction is ascribed to the defects in the local coordination environment of the two surfaces as the reactivity of atoms surrounding a vacant site is reported to increase due to their reduced coordination state. [72]. The carbonation reaction occurs through a concerted C-O bond formation with the surface oxygen atoms (sp3 hybridization of the C atom) and a proton transfer to form an H 2 O molecule.…”
Section: The Reactivity Of Pure Scco 2 With Portlandite Surfacesmentioning
confidence: 99%